Angiotensin-Receptor-Associated Protein Modulates Ca2+ Signals in Photoreceptor and Mossy Fiber cells - Barro-Soria, Rene; Caicedo, Alejandro; Jaegle, Herbert; Merkel, Laura; Zhao, Na; Knop, Gabriel; Gierke, Kaspar; Dannullis, Andrea; Castrop, Hayo; Brandstätter, Johann Helmut; Kirchhoff, Frank; Feigenspan, Andreas; et al. (Scientific Reports, 2019)
Fast, precise and sustained neurotransmission requires graded Ca2+ signals at the presynaptic terminal. Neurotransmitter release depends on a complex interplay of Ca2+ fluxes and Ca2+ buffering in the presynaptic terminal that is not fully understood. Here, we show that the angiotensin-receptor-associated protein (ATRAP) localizes to synaptic terminals throughout the central nervous system. In the retinal photoreceptor synapse and the cerebellar mossy fiber-granule cell synapse, we find that ATRAP is involved in the generation of depolarization-evoked synaptic Ca2+ transients. Compared to wild type, Ca2+ imaging in acutely isolated preparations of the retina and the cerebellum from ATRAP knockout mice reveals a significant reduction of the sarcoendoplasmic reticulum (SR) Ca2+-ATPase (SERCA) activity. Thus, in addition to its conventional role in angiotensin signaling, ATRAP also modulates presynaptic Ca2+ signaling within the central nervous system.
CRIS-Team WoS Importer:2020-02-07

GlyT1 determines the glycinergic phenotype of amacrine cells in the mouse retina - Eulenburg, Volker; Knop, Gabriel; Sedmak, Tina; Schuster, Stefanie; Hauf, Katharina; Schneider, Julia; Feigenspan, Andreas; Joachimsthaler, Anneka; Brandstätter, Johann Helmut (Brain Structure & Function, 2018)
The amino acid glycine acts as a neurotransmitter at both inhibitory glycinergic and excitatory glutamatergic synapses predominantly in caudal regions of the central nervous system but also in frontal brain regions and the retina. After its presynaptic release and binding to postsynaptic receptors at caudal glycinergic synapses, two high-affinity glycine transporters GlyT1 and GlyT2 remove glycine from the extracellular space. Glycinergic neurons express GlyT2, which is essential for the presynaptic replenishment of the transmitter, while glial-expressed GlyT1 was shown to control the extracellular glycine concentration. Here we show that GlyT1 expressed by glycinergic amacrine cells of the retina does not only contribute to the control of the extracellular glycine concentration in the retina but is also essential for the maintenance of the glycinergic transmitter phenotype of this cell population. Specifically, loss of GlyT1 from the glycinergic AII amacrine cells impairs AII-mediated glycinergic neurotransmission and alters regulation of the extracellular glycine concentration, without changes in the overall distribution and/or size of glycinergic synapses. Taken together, our results suggest that GlyT1 expressed by amacrine cells in the retina combines functions covered by neuronal GlyT2 and glial GlyT1 at caudal glycinergic synapses.
EVALuna2:35241